Cold tolerance in terrestrial invertebrates inhabiting subterranean habitats - Tone Novak; Nina Šajna; Estera Antolinc; Saška Lipovšek; Dušan Devetak; Franc Janžekovič (International Journal of Speleology, 2014)
Most organisms are able to survive shorter or longer exposure to sub-zero temperatures. Hypothetically, trogloxenes characterized as not adapted, and troglophiles as not completely adapted to thermally stable subterranean environment, have retained or partially retained their ability to withstand freezing, while most troglobionts have not. We tested this hypothesis experimentally on 37 species inhabiting caves in Slovenia, analyzing their lower lethal temperatures in summer and winter, or for one season, if the species was not present in caves during both seasons. Specimens were exposed for 12 hrs to 1°C-stepwise descending temperatures with 48 hr breaks. In general, the resistance to freezing was in agreement with the hypothesis, decreasing from trogloxenes over troglophiles to troglobionts. However, weak resistance was preserved in nearly all troglobionts, which responded in two ways. One group, withstanding freezing to a limited degree, and increasing freezing tolerance in winter, belong to the troglobionts inhabiting the superficial subterranean habitats. The other group, which equally withstand freezing in summer and winter, inhabit deep subterranean or other thermally buffered subterranean habitats. Data on cold resistance can thus serve as an efficient additional measure of adaptation to particular hypogean environments.